(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Affixes—morphemic elements attached to roots—play a vital role in word formation and grammatical function in many languages. This paper explores the classification of affixes from both structural and functional viewpoints, focusing on the typologies in English and Uzbek. Affixes are broadly categorized into prefixes, suffixes, infixes, and circumfixes based on their position relative to root words. Functionally, they can serve derivational or inflectional purposes, affecting either the lexical category or grammatical meaning. Through comparative analysis, this study highlights how affixation contributes to the flexibility and expressiveness of languages. Additionally, it emphasizes the importance of affix classification in language learning, teaching, and computational linguistics.